How Subsistence Communities Reconfigure Livelihood Systems in Response to Climate Change: A Coupled-Systems Perspective - Chakrabarti, Ronika (My University, 2022)
A defining societal challenge in the era of climate change is ensuring consumption adequacy in subsistence communities. To understand the intricacies of this challenge, we have conducted an ethnographic study of a low-income community that relies on subsistence fishing to maintain consumption adequacy. Based on our data analysis, we advance a conceptualization of subsistence livelihood systems that models the tight coupling among its three constituent subsystems: the market system, the social system, and the environmental system. These three subsystems are highly interdependent and operate in concert to maintain consumption adequacy. We then show how climate change-induced environmental disruptions threaten consumption adequacy by disequilibrating livelihood systems in subsistence settings, as well as unpack the self-directed adaptation and mitigation strategies employed by the community in response to the threat of consumption inadequacy. These response strategies create feedback loops to either preserve or attenuate the tight coupling among the three subsystems.
PUBLISHED
Keywords: subsistence; poverty; consumption inadequacy; environmental disruption; climate change; Inclusive Society; International Development; International Integration; Climate Change; Developing Countries; Economic Development; Marketing; Other; Poverty